WOMEN'S EMPOWERMENT THROUGH DIGITAL MARKETING PROCESSED PRODUCTS OF AMPLANG CRACKERS WITH PAYUS FISH IN THE FISHING VILLAGE OF SALIRA VILLAGE - Munawaroh, Munawaroh; Mahfudah, Siti Nazihah; Aulia, Rifdah; Ma'arif, Muhamad Syamsul; Aisyah, ⁠Siti Nurul; Kusuma, Jaka Wijaya; Widodo, Wahyu; Komarudin, Mamay; Mutoharoh, Mutoharoh; Idayu, Riyanthi (International Journal of Engagement and Empowerment (IJE2), 2024)
This community service activity is motivated by the needs of female MSME actors in Salira Village to increase the competitiveness of amplang cracker products in the digital market. Although this product has tremendous market potential, the challenges in using digital technology for marketing hinder product reach and sales. This activity aims to introduce and implement effective digital marketing strategies so that MSME actors can maximize their market potential and improve local economic welfare. The implementation methods include initial needs assessment, digital marketing training through workshops and practical sessions, implementation of strategies on processed fish products, and evaluation of results using surveys and sales analysis. The activity results showed a significant increase in digital marketing understanding and skills among MSME actors, with an average increase in turnover of 30% in the three months after the training. In addition, establishing an online community forum strengthens support between MSME actors. This activity increases digital marketing capacity and strengthens social networks, providing a sustainable positive impact on local economic development